ANALYSIS OF THE MAIN OPERATING COSTS OF AIRLINES AS A STRATEGY TO ENABLE A LOW COST COMPANY IN BRAZIL - Torres, Victor Scarparo; Bergamini, Wellington Tacone; Cella, Daltro (Revista Interface Tecnológica, 2020)
This paper aims to present the main costs related to the operations of a low cost airline and describe the main variables that can make this business model in Brazil feasible. Although there is no legal regulation that subdivides the airline sector into traditional and low cost, the low cost nomenclature is characterized by a low price on airfare by cutting costs in the flight process, increasing the number of tickets sold and increasing in airline revenue for charging services such as food, drinks and special services (entertainment, internet). The methodology was based on a bibliographic review, based on theoretical references published in electronic media, such as scientific articles and websites on the operating costs of airlines and in accordance with the legislation of the airline sector. Aviation yearbooks, portfolios of the aerial panorama were used to collect the data, in addition to sources and legislation provided mostly by the portal of the National Civil Aviation Agency. To implement this low-cost strategy, it is necessary to reduce operating costs by updating Brazilian legislation for the sector, reducing taxes on aviation kerosene, changes in legislation to reduce excess lawsuits against airlines and greater standardization of aircraft by airlines.
Keywords: Airlines.; Low cost.; Civil aviation.